The Effect of Social Media, Marketing Communication, and Customer Reviews on Purchasing Decisions in E-Commerce among Generation Z Students in Medan City - Achiruddin Siregar; Moh. Zaini; Dwi Wahyono; Yuni Candra; Dikdik Purwadisastra (Yayasan Kawanad, 2026)
E-commerce purchasing behavior among Generation Z warrants serious scholarly attention — this cohort constitutes the largest segment of active digital users whose decision-making processes are shaped in ways older consumer models do not adequately capture. This study examined the influence of social media, marketing communications, and customer reviews on e-commerce purchasing decisions in Medan City, focusing on Generation Z students at several private universities. A quantitative survey design was employed, with data collected via structured questionnaires distributed to 100 respondents and analyzed using SPSS 26, encompassing validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination. Each independent variable returned a positive and statistically significant effect on purchasing decisions. The simultaneous test confirmed that the three variables together exert a positive and significant influence on e-commerce purchasing decisions in Medan City. The Adjusted R Square of 0.417 indicates that 41.7% of the variance is accounted for by the model; the remaining 58.3% reflects variables outside the model's scope, including on-time delivery and discount practices.